Enhanced liver fibrosis score as a noninvasive biomarker in hepatitis C virus patients after direct-acting antiviral agents - Cossiga, Valentina; La Civita, Evelina; Bruzzese, Dario; Guarino, Maria; Fiorentino, Andrea; Sorrentino, Rosanna; Pontillo, Giuseppina; Vallefuoco, Luca; Brusa, Stefano; Montella, Emma; Terracciano, Daniela; Morisco, Filomena; et al. (Frontiers in Pharmacology, 2022)
Background: In more than 90% of chronic viral hepatitis C (HCV) patients treated with direct-acting antiviral agents (DAAs) sustained viral response (SVR) was observed. Unfortunately, there are subgroups of subjects who display enduring liver fibrosis and are at high risk to develop hepatocellular carcinoma (HCC). Thus, liver fibrosis evaluation during the follow-up of these patients plays a pivotal role. The gold standard to evaluate hepatic fibrosis is liver biopsy an invasive procedure, imaging techniques and serum biomarkers were proposed as more safe procedures. Objectives: In this study we evaluated the concordance of Transient Elastography (TE) with ELF score (Enhanced Liver Fibrosis) in a cohort of patients with HCV before and after direct-acting-antiviral (DAAs) treatment. ELF score has been validated in other chronic liver diseases; evidence is not available in HCV patients treated with DAAs. Study design: We prospectively recruited all consecutive HCV patients candidate to DAAs therapy at University of Naples “Federico II” between April 2015 and July 2016. All participants underwent TE and had their ELF score assessed at baseline and at SVR24. Results: One-hundred-nineteen patients were treated with DAAs and 94.1% of them reached SVR. 55.5% of patients were males with a mean age of 64.7±9.6 years. TE results revealed that 12 patients (10%) had F1-2 mild/moderate fibrosis, 107 (90%) had F3-4 advanced fibrosis. At baseline, SVR24 and SVR48, the concordance between ELF test and TE was poor: 0.11 (p= 0.086), 0.15 (p=0.124) and 0.00 (p=0.002) respectively. However, at SVR24 and SVR 48 both methods showed a significant amelioration of liver fibrosis compared to baseline (p<0.001). In addition, both ELF index and TE were significantly associated with portal hypertension at baseline, but not with varices and ascites. Conclusions: Our findings suggested that ELF test can predict independently of TE changes in liver fibrosis. In case of TE unavailability, ELF score could represent an appropriate substitute and for HCV therapy “simplification” ELF score could help to reduce TE exams. Notably, in the context of COVID-19 pandemic, ELF testing should be encouraged to reduce unnecessary access to the hospital and prolonged physical contact.